2011
DOI: 10.1007/s10709-012-9636-y
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic differentiation via 2n reduction and a finding of a case of triploidy in anurans of the genus Engystomops (Anura, Leiuperidae)

Abstract: The genus Engystomops is divided into two groups, namely the Duovox clade and the Edentulus clade. The species of Edentulus clade have karyotypes with 2n = 22, while E. pustulatus and E. puyango, which belong to Duovox clade, have 2n = 20. To investigate if 2n = 20 is a synapomorphy of Duovox clade, we cytogenetically analyzed all the species of this group, except for E. puyango, in the present study. All of them had 2n = 20, differing from the species of Edentulus clade. Since the species already karyotyped o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
1
3
0
3
Order By: Relevance
“…A distinctive feature of tadpoles of E. guayaco is the presence of a conspicuous brown spot on the tail tip (Ron et al, 2005). We confirmed this character in our analyses for this species, but also found a similar pattern in tadpoles of E. randi , considered a very similar species to E. guayaco (Targueta et al, 2011). These two species, along with E. coloradorum and E. montubio , formed the clade Brevivox (Ron et al, 2006), characterized by small‐sized and morphologically conservative species, except for E. coloradorum (Cannatella & Duellman, 1984; Ron et al, 2004, 2005, 2006).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A distinctive feature of tadpoles of E. guayaco is the presence of a conspicuous brown spot on the tail tip (Ron et al, 2005). We confirmed this character in our analyses for this species, but also found a similar pattern in tadpoles of E. randi , considered a very similar species to E. guayaco (Targueta et al, 2011). These two species, along with E. coloradorum and E. montubio , formed the clade Brevivox (Ron et al, 2006), characterized by small‐sized and morphologically conservative species, except for E. coloradorum (Cannatella & Duellman, 1984; Ron et al, 2004, 2005, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…Engystomops guayaco and E. randi are cryptic species that occur in sympatry (Ron et al, 2005) but differ in their calls. Additionally, Targueta et al (2011) found distinctive cytogenetic patterns in E. randi , such as an interstitial C‐band in chromosome 10, that is absent in E. guayaco . Interesting, these two species exhibit distinctive diagnoses in the buccal cavities.…”
Section: Discussionmentioning
confidence: 99%
“…This report is the first record of spontaneous autopolyploidy in a natural population of a diploid hylid species. This phenomenon is infrequent among anurans and has been observed only in eight species, Amietophrynus poweri (Bufonidae, [ 83 ]), Engystomops coloradum (Leptodactylidae, [ 84 ]), Eupsophus vertebralis (Alsodidae, [ 85 ]), Holoaden luederwaldti (Craugastoridae, [ 86 ]), Leiopelma hochstetteri (Leiopelmatidae, [ 87 ]), Lithobates palustris and L . pipiens (Ranidae, [ 88 , 89 ]), Odontophrynus americanus (Odontophrynidae, [ 90 ]), and Xenopus tropicalis (Pipidae, [ 80 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic data provide a powerful tool for the evaluation of the taxonomic (Cuevas, 2008; Fávero et al , 2011; Funk et al , 2012) and evolutionary relationships (Veiga-Menoncello et al , 2014) among anuran species. The understanding of chromosomal characters helps to identify synapomorphies (Cunningham and Cherry, 2004; Targueta et al , 2012; Suárez et al , 2013; Ferro et al , 2018) and homoplasies (Cardozo et al , 2011), and when combined with molecular phylogenetic inferences, these can contribute to the understanding of the role of chromosomal rearrangements in the diversification of a lineage (Veiga-Menoncello et al , 2014).…”
mentioning
confidence: 99%